Population trends of the Southern Rockhopper Penguin (Eudyptes chrysocome chrysocome) at the northern limit of its breeding range: Isla Pingüino, Santa Cruz, Argentina - Gandini, Patricia Alejandra; Millones, Ana; Morgenthaler, Annick; Frere, Esteban (Polar Biology)
During the last century, there has been a steady decline in the global breeding population of Eudyptes chrysocome chrysocome, and this species has been exposed to many different threats. However, the small breeding population of Isla Pingüino, Argentina, increased since its discovery in 1985 until 1990. To determine whether this population continued to grow, we assessed its trend over a 30-year period and estimated its breeding success. This study shows a strong increase in the population in Isla Pingüino with an annual growth rate of more than 7 %, throughout the 30-year study period. The threats that are affecting seabird populations in other areas seem to have no negative effects on this breeding population. In particular, tourism, which has grown exponentially during the survey period, appears to not have had a negative effect on the settlement of new pairs, the number of breeding pairs and their breeding success. We suggest that the population increase in Isla Pingüino might have been facilitated by an immigration of breeding adults from nearby breeding sites such as Falkland Islands (Malvinas). Fil: Gandini, Patricia Alejandra. Universidad Nacional de la Patagonia Austral. Unidad Académica Caleta Olivia. Centro de Investigaciones Puerto Deseado; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Millones, Ana. Universidad Nacional de la Patagonia Austral. Unidad Académica Caleta Olivia. Centro de Investigaciones Puerto Deseado; Argentina Fil: Morgenthaler, Annick. Universidad Nacional de la Patagonia Austral. Unidad Académica Caleta Olivia. Centro de Investigaciones Puerto Deseado; Argentina Fil: Frere, Esteban. Universidad Nacional de la Patagonia Austral. Unidad Académica Caleta Olivia. Centro de Investigaciones Puerto Deseado; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina